Interaksi Pemberian Zat Antioksida dan Perangsang Tumbuh pada Ransum terhadap Penampilan Ayam Pedaging - S. Iskandar (Buletin Ilmu Makanan Ternak, 1990)
The effect of inclusion of an anti coccidial drug (lasalocid) and supplementation of growth promotant (bayonox) in broiler chicken diets were assessed by a feeding trial. Three levels of lasalocid (60,75 and 90 ppm) and one level of bayonox (10 ppm) were included in the diets. The birds were fed ad libitum for a period of 42 days. There was significant effect of lasalocid supplemention on either growth rate, food consumption or food conversion ratio. However, growth rate tended to increase on 60 ppm lasalocid supplementation. The addition of bayonox significantly (P<0.05) increased growth rate, whilst there were no significant interaction effect of supplementation of lasalocid and bayonox on growth rate, food consumption and food conversion ratio.